Letter to the editor - Díaz Untoria, José A. (Cuban Journal of Agricultural Science, 2016)
Organizations, besides having the technological means for generating, synthetizing and transferring knowledge, should have systems that facilitate the flow of this knowledge and the generation of new researches. An example of the previously exposed idea is the Cuban Journal of Agricultural Science, which belongs to the Ministry of Higher Education, accredited by CITMA since 2000 and cited in international databases like EBESCO, Latindex, AGRIS, Redalyc and SCOPUS.